2015
DOI: 10.1371/journal.pone.0138289
|View full text |Cite
|
Sign up to set email alerts
|

A Glaucoma-Associated Variant of Optineurin, M98K, Activates Tbk1 to Enhance Autophagosome Formation and Retinal Cell Death Dependent on Ser177 Phosphorylation of Optineurin

Abstract: Certain missense mutations in optineurin/OPTN and amplification of TBK1 are associated with normal tension glaucoma. A glaucoma-associated variant of OPTN, M98K, induces autophagic degradation of transferrin receptor (TFRC) and death in retinal cells. Here, we have explored the role of Tbk1 in M98K-OPTN-induced autophagy and cell death, and the effect of Tbk1 overexpression in retinal cells. Cell death induced by M98K-OPTN was dependent on Tbk1 as seen by the effect of Tbk1 knockdown and blocking of Tbk1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 72 publications
1
41
0
1
Order By: Relevance
“…Another study linked loss-of-function TBK1 mutations to both ALS and FTD (21). Finally, mutations in both TBK1 and OPTN are causal for both ALS and glaucoma (20,31). In this study, we observed that the ALS-associated mutants TBK1-E696K, OPTN-E478G, and OPTN-Q398X all interfere with efficient autophagic engulfment of damaged mitochondria.…”
Section: Discussionmentioning
confidence: 51%
“…Another study linked loss-of-function TBK1 mutations to both ALS and FTD (21). Finally, mutations in both TBK1 and OPTN are causal for both ALS and glaucoma (20,31). In this study, we observed that the ALS-associated mutants TBK1-E696K, OPTN-E478G, and OPTN-Q398X all interfere with efficient autophagic engulfment of damaged mitochondria.…”
Section: Discussionmentioning
confidence: 51%
“…In a recent work, our laboratory reported the dysregulation of autophagy with aging and in TM cells isolated from glaucoma cadaver eyes 17 . A connection between autophagy and neurodegeneration in glaucoma is strongly supported from the discovery that the optineurin and TANK Binding Kinase (TBK1), normal tension glaucoma (NTG)-associated genes, are essential players in the autophagic degradation of damaged mitochondria, a process known as mitophagy 20,21 . Activation of autophagy in RGCs in response to injury (ON transection) or elevated IOP (acute or chronic) has been reported in different induced models of experimental glaucoma 2228 .…”
Section: Introductionmentioning
confidence: 99%
“…OPTN point mutations have been linked to glaucoma or ALS and evidence implicates impaired autophagy and compromised mitochondrial integrity as key pathogenic mechanisms (Chalasani et al, 2014;Sirohi et al, 2015;Wong and Holzbaur, 2014). Autophagy disruptions and mitochondrial dysfunction occur in PD and are likely key pathogenic events in the earliest disease stages (Parker et al, 1989;Tan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, metaanalysis of genome-wide association studies shows that single nucleotide polymorphisms in OPTN may increase PD risk. Specifically, the M98K mutation, which likely affects OPTNmediated autophagy, causes glaucoma and was identified as a PD risk modulator (Lill et al, 2012;Sirohi et al, 2015). Thus, mechanistic and genetic data provide a strong rationale for investigation in PD.…”
Section: Discussionmentioning
confidence: 99%